Mitigation of doxorubicin-induced liver toxicity in mice breast cancer model by green tea and Moringa oleifera combination: Targeting apoptosis, inflammation, and oxidative stress - Abdulrahman H. Laftah; Nawfal Alhelfi; Sadeq K. Al Salait; Ammar B. Altemimi; Mohammad Reza Tabandeh; Efstathia Tsakali; Jan F.M. Van Impe; Ahmed A. Abd El-Maksoud; Tarek Gamal Abedelmaksoud (Journal of Functional Foods)
This study evaluated the effect of green tea and Moringa oleifera extracts (at 1 % and 2 % concentration) on DOX-treated breast cancer mice. 36 Balb/C female mice with breast cancer were split into healthy mice, 4 T1 cell cancer-induced, and Doxorubicin-induced malignancies. Assessments included weight, tumor size, liver enzymes, antioxidant enzymes, oxidative stress markers, pro-inflammatory cytokines, gene expressions for apoptosis and inflammation (BAX, BCL2, NLRP3, NFKB), and liver tissues were histopathologically examined. DOX increased liver enzymes and may have damaged the liver. The hepatoprotective effects of these extracts, notably at 2 %, were apparent in their enzyme reduction. Liver CAT, GPX, and SOD activity increased and TOS and OSI levels decreased due to the extracts. Additionally, the herbal treatment lowered pro-inflammatory cytokine levels and regulated apoptosis-related gene expression, lowering BAX and increasing BCL2, promoting cell survival, and reducing inflammation. Herbal extracts can reduce NLRP3/NFKB expression in DOX-treated mice's livers, depending on dosage. Histopathological evaluation showed that highly-dose therapy reduced hepatocyte degradation, inflammatory cell infiltration, localized necrosis, and blood vessel congestion. Finally, green tea and Moringa oleifera extracts protect against DOX-induced hepatotoxicity.